The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1042/bj20061168
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the dimerization domain of the ferric uptake regulator (Fur) of Pseudomonas aeruginosa

Abstract: The functional properties of the recombinant C-terminal dimerization domain of the Pseudomonas aeruginosa Fur (ferric uptake regulator) protein expressed in and purified from Escherichia coli have been evaluated. Sedimentation velocity measurements demonstrate that this domain is dimeric, and the UV CD spectrum is consistent with a secondary structure similar to that observed for the corresponding region of the crystallographically characterized wild-type protein. The thermal stability of the domain as determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
(70 reference statements)
5
7
0
Order By: Relevance
“…This is evident in the metal ion-amino acid distances in Table 1 and Fig. 4 did not find any zinc at close proximity to Cys132 or Cys137, in agreement with previous experimental reports for P. A. Fur [17,22] . From the metal ion-residue distances ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This is evident in the metal ion-amino acid distances in Table 1 and Fig. 4 did not find any zinc at close proximity to Cys132 or Cys137, in agreement with previous experimental reports for P. A. Fur [17,22] . From the metal ion-residue distances ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…The Zn 2? ion was given the role of inducing and preserving the Fur dimer three dimensional structure [2,10,15,17,19,22]. Residues on the Fur dimer can be classified according to their sensitivity to metal ions as follows:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioinformatics analysis revealed that this protein comprises two conserved domains in the family of Fur/Zur proteins: a hypothetical DNA-binding motif at its N terminus and a putative C-terminal dimerizing module (2). Sensitivity assays with divalent transition metal ions demonstrated that gene 310 is a zinc-responsive regulator gene, referred to as zur (Fig.…”
Section: Discussionmentioning
confidence: 99%